Use of Global Risk Score for Cardiovascular Evaluation of Rural Workers in Southern Brazil - Marta Regina Cezar-Vaz; Clarice Alves Bonow; Marlise Capa Verde Almeida de Mello; Daiani Modernel Xavier; Jordana Cezar Vaz; Maria Denise Schimith (The Scientific World Journal)
The objectives of the present study were to classify the cardiovascular evaluation of rural workers through the Global Risk Score and analyze the intensity of the relationship between the classification and the variables of the score. A descriptive study was developed with 38 rural workers from the extreme southern Brazil. Data collection was performed through an interview and verification of anthropometric measurements and arterial blood pressure. Data were analyzed descriptively and inferentially using the Spearman correlation test. The overall 10-year cardiovascular risk classification using the Framingham global score showed a predominance of low risk (n=22; 57.9%); however, 11 rural workers (28.9%) had a high cardiovascular risk. Spearman’s correlation analysis showed significance between the Global Risk Score and gender (rho = 0.623, p≤0.001), age (rho = 0.783, p≤0.001), systolic blood pressure (rho = 0.545, p≤0.001), and smoking (rho = 0.483, p=0.002). These results show that rural workers need attention with regard to components that may put them at risk for cardiovascular disease. This study may help in the early diagnosis and more effective actions on the risk factors for cardiovascular disease.